Urinary CD163 is a marker of active kidney disease in childhood-onset lupus nephritis. (12th August 2022) - Inthavong, Haleigh; Vanarsa, Kamala; Castillo, Jessica; Hicks, M John; Mohan, Chandra; Wenderfer, Scott E
Abstract: Objective: The objective of this study was to evaluate the utility of urine CD163 for detecting disease activity in childhood-onset SLE (cSLE) patients. Methods: Sixty consecutive pediatric patients fulfilling four or more ACR criteria for SLE and 20 healthy controls were recruited for testing of urinary CD163 using ELISA. SLE disease activity was assessed using the SLEDAI-2K. Results: Urine CD163 was significantly higher in patients with active LN than inactive SLE patients and healthy controls, with receiver operating characteristics area under the curve values ranging from 0.93 to 0.96. LN was ascertained by kidney biopsy. Levels of CD163 significantly correlated with the SLEDAI, renal SLEDAI, urinary protein excretion and C3 complement levels. Urine CD163 was also associated with high renal pathology activity index and chronicity index, correlating strongly with interstitial inflammation and interstitial fibrosis based on the examination of concurrent kidney biopsies. Conclusion: Urine CD163 emerges as a promising marker for identifying cSLE patients with active kidney disease. Longitudinal studies are warranted to validate the clinical utility of urine CD163 in tracking kidney disease activity in children with lupus.